Teacher Education: A Comparative Analysis Between Colleges of Education and Universities with Implications for Ghana - Richard Lionel Gorni; Syaefudin Saud (GoAcademica Research & Publishing, 2023)
This comparative analysis examines the development and value orientations of colleges of education and universities in Ghana, with implications for teacher education. The study provides a historical overview of the evolution of these institutions in Ghana, exploring the different periods in which they emerged and their associated value orientations. It addresses the core question of how teacher education can achieve excellence comparable to universities while retaining the relevant values of colleges of education in the context of a knowledge society. By conducting a comparative historical analysis of some Western societies, the study identifies four distinct models of teacher education that have historically emerged and evaluates them comparatively. Finally, the research compares teacher education in Singapore and Ghana, suggesting that a university of education model may be uniquely suitable for the Ghanaian context and culturally viable in an African environment.